A REVIEW: THE USE OF SOME PGR on MICROPOPAGATION of Pogostemon cablin Benth. - Zahara, Meutia; Suryady, Suryady (Jurnal Biologi Sains dan Kependidikan, 2022)
ABSTRACTAceh patchouli (Pogostemon cablin Benth.) is an aromatic plant producing essential oils demanded in the worldwide, which is belongs to Labiate family. This plant also well known as patchouli, the leaves contain oils that demanded in the perfume industry, aromatherapy, anti-microbial, anti-depressed, anti-inflammatory, and antioxidant. The production of Pogostemon cablin Benth has decreased in recent years, the characteristic of seedling propagated vegetative conventional means are not uniform; susceptible to pest and take long time. Therefore, propagation through tissue culture is desirable. Micropropagation or tissue culture techniques can produce plants that are disease-resistant, uniform, and large production in a short time. Tissue culture carried out aseptically and using the sterile medium supplemented with Plant Growth Regulators (PGR). This paper endeavor to include some important investigations based on the PGR used in micropropagation of Pogostemon cablin Benth. Keywords: PGR, Micropopagation, Pogostemon cablin Benth